Breaching of Mustang Island in response to the 8.2 ka sea-level event and impact on Corpus Christi Bay, Gulf of Mexico: Implications for future coastal change. (January 2018) - Ferguson, Shannon; Warny, Sophie; Anderson, John B; Simms, Alexander R; White, Crawford
The results from an investigation of the coupled Mustang Island–Corpus Christi Bay complex, Gulf of Mexico, shows that the island was eliminated as an effective salinity barrier between 8.86 and 8.17 ka. This event is recorded by a 5-fold increase in dinoflagellate cysts within Corpus Christi Bay. During this time, the bay-head delta shifted 15 km landward and oyster reefs within the bay died off. Our age model indicates that this event most likely resulted from the most rapid period of eustatic rise of the Holocene, which peaked at 8.18–8.31 ka. This event is attributed to late-stage ice sheet disintegration, particularly in North America, by the rapid draining of Lake Agassiz–Ojibway. Local glacial-isostatic factors resulted in a sea-level rise of only 0.2–0.56 m in the western Gulf of Mexico, which was less than needed to submerge the barrier. Rather, it was the marked nature of this sea-level rise that led to the virtual destruction of Mustang Island as an effective salinity barrier. These results provide an analog for predicting coastal morphodynamic response to accelerated sea-level rise and emphasize the need for better understanding of barrier response to sea-level rise and developing improved numerical models for predicting future changes to coastal barrier shorelines.